Thermal-hydraulic analysis of a fluoride-salt-cooled pebble-bed reactor with CFD methodology. (August 2016) - Ge, Jian; Wang, Chenglong; Xiao, Yao; Tian, Wenxi; Qiu, Suizheng; Su, G.H.; Zhang, Dalin; Wu, Yingwei
Abstract: The Fluoride Salt Cooled High Temperature Reactor (FHR) is an innovative concept reactor that inherits the technical foundation and advantages of the six optional generation-IV reactors and pressurized water reactors, which is mainly in process in both China and the United States. In this paper, the porous and realistic modeling approaches are adopted to analyze the thermal hydraulic characteristics of a FHR core and a unit segment of pebbles in the core respectively. The distributions of temperature and pressure of the fluoride salt, as well as the reflector temperature profile, are obtained using the porous model. The detailed local flow and heat transfer are investigated by the realistic modeling method for the locations which may have the maximum coolant temperature based on the results of the porous model. The profiles of temperature, velocity, pressure and Nusselt number (Nu) of the coolant on the surface of the pebble are also obtained and analyzed. Numerical results showed that the flow field between the fuel pebbles is complex including secondary flow and back-flow phenomenon, which are hard to measure by experiments. This work can provide useful information for the experimental and mechanism research of FHRs. Highlights: Thermal hydraulic characteristics of FHR are studied by both porous and realistic approaches. The global coolant temperature and pressure distribution and reflector temperature profile are obtained by porous model. The detailed local flow and heat transfer for a unit segment of pebbles are investigated using realistic approach.